Bridging the Gap : Teaching Adaptations Across the Disciplines and Sharing Content for Curriculum Renewal (The Adapt Project) : Final Report. - Wilson, Felix; Whelehan, Imelda; Sadler, David (Office for Learning and Teaching, 2013)
Final report from a project where a key aim is to identify a community of academics involved in the teaching of Adaptation Studies, and encourage them to share resources via a repository. This will allow scholars located across several disciplines to benefit from others' experiences in delivering and assessing a cross-disciplinary subject, and profit from peer review by sharing materials. The project partners, both Adaptations scholars and Open Educational Resource specialists, allow the pooling of expertise and the testing of strategies to populate a repository, as well as constructing a toolkit to facilitate easy use, while exploring the use of Creative Commons licensing. The project anticipates challenges around copyright, gaining trust from those who might share materials, but is well-placed to learn lessons from existing feasibility studies and projects in Australia and beyond. The resulting hub will encourage further OER initiatives in universities, offer opportunities to improve the quality and range of teaching materials and provide a resource bank for students.